Corynebacterium striatum Bacteremia Associated with a Catheter-Related Blood Stream Infection - Ueno Daisuke; Tomohiro Oishi; Kunikazu Yamane; Kihei Terada (Case Reports in Infectious Diseases)
A 49-year-old woman visited our emergency department because of exertional dyspnea due to severe left ventricular functional failure. It progressed to disseminated intravascular coagulation and disturbance of consciousness on day 67 of admission. Gram-positive bacilli were detected from two different blood culture samples on day 67 of admission. An API-Coryne test and sequencing (1~615 bp) of the 16S rRNA gene were performed, and the strain was identified as Corynebacterium striatum. The bacterium was detected from the removed central venous catheter tip too, and the patient was diagnosed with catheter-related bloodstream infection by C. striatum. However, treatment was not effective, and the patient died on day 73 of admission.